Antioxidant adjustments of olive trees (Olea europaea) under field stress conditions - Araújo, Márcia (2018)
Extreme climate events are increasingly frequent, and the 2017 summer was particularly critical in the Mediterranean region. Olive is one of the most important species of this region, and these climatic events represent a threat to this culture. However, it remains unclear how olive trees adjust the antioxidant enzymatic system and modulate the metabolite profile under field stress con-ditions. Leaves from two distinct adjacent areas of an olive orchard, one dry and the other hydrated, were harvested. Tree water status, oxidative stress, antioxidant enzymes, and phenolic and lipo-philic metabolite profiles were analyzed. The environmental conditions of the 2017 summer caused a water deficit in olive trees of the dry area, and this low leaf water availability was correlated with the reduction of longâ€ chain alkanes and fatty acids. Hydrogen peroxide (H2O2) and superoxide radical (O2•–) levels increased in the trees collected from the dry area, but lipid peroxidation did not augment. The antioxidant response was predominantly marked by guaiacol peroxidase (GPOX) activity that regulates the H2O2 harmful effect and by the action of flavonoids (luteolinâ€ 7â€ Oâ€ glucu-ronide) that may act as reactive oxygen species scavengers. Secoiridoids adjustments may also con-tribute to stress regulation. This work highlights for the first time the protective role of some metabolite in olive trees under field drought conditions.